1986
DOI: 10.1017/s0022029900024687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the formation of deposit from milk on heated surfaces during ultra high temperature processing

Abstract: Investigation of the effect of pH on the formation of deposit from milk during ultra high temperature treatment using a plate-type plant showed that deposit formation was greatly increased when the pH of whole milk was reduced to 6-54, irrespective of whether the adjustment was made through the addition of HC1 or lactic acid. Most of the increase in deposition took place in the higher temperature sections of the plant. Conversely, an increase in milk pH to 6-8 using NaOH resulted in considerably less deposit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 20 publications
3
9
0
1
Order By: Relevance
“…Although above pH 6.5 the rate of 6-lactoglobulin denaturation will increase, the amount of molecular unfolding associated with denaturation will be reduced, allowing fewer intermolecular disulphide exchange reactions, and thus decreased aggregation. The importance of aggregation is further demonstrated by Skudder et al (1986) who found that the extent of denaturation was similar at pH 5.0 and 7.0. However, fouling amounts are significantly different at the two pH values, as is the extent of aggregation.…”
Section: The Effect Of Ph On P-lactoglobulin Denaturation and Proteinmentioning
confidence: 88%
See 1 more Smart Citation
“…Although above pH 6.5 the rate of 6-lactoglobulin denaturation will increase, the amount of molecular unfolding associated with denaturation will be reduced, allowing fewer intermolecular disulphide exchange reactions, and thus decreased aggregation. The importance of aggregation is further demonstrated by Skudder et al (1986) who found that the extent of denaturation was similar at pH 5.0 and 7.0. However, fouling amounts are significantly different at the two pH values, as is the extent of aggregation.…”
Section: The Effect Of Ph On P-lactoglobulin Denaturation and Proteinmentioning
confidence: 88%
“…However, it is possible to use DSC evidence, together with that for fouling, to suggest the controlling mechanism for deposit formation. Fouling in pasteurization and UHT plants increases rapidly below pH 6.6 (Hege & Kessler, 1986;Skudder et al, 1986). Hege & Kessler (1986) found deposit formation to be a maximum at pH 5.1.…”
Section: The Effect Of Ph On P-lactoglobulin Denaturation and Proteinmentioning
confidence: 99%
“…For instance the influence of surface characteristics on milk deposit formation was assessed by Britten, Green, Boulet, and Paquin (1988), and they found that the adhesion of the deposit was weaker for surfaces with lower surface energy. Skudder, Brooker, Bonsey, and Alvarez-Guerrero (1986) investigated the effect of pH on the deposit formation from milk during high temperature treatment using a plate heat exchanger. In this case an increase in deposition was observed when the pH of whole milk was reduced to 6.54, while a reduction of deposit formation occurred with an increase of the milk pH above 6.8.…”
Section: Introductionmentioning
confidence: 99%
“…Fouling not only results in higher operating costs but has an adverse effect on environment also (Brinkmann, 1986;Graßhoff, 1997;Sandu & Singh, 1991;. Various factors influencing the deposit formation in UHT processing include fore-warming of milk (Bell & Senders, 1944;Lyster, 1965;Burton, 1966;Mottar & Moermans, 1988;Patil & Reuter, 1986a, 1986b, prepasteurization (Lalande, Tissier, & Corrieu, 1984), pH of milk (Burton, 1966;Gordon, Hankinson, & Carver, 1968;Gynning, Thome, & Samuelsson, 1958;Kastanas, Lewis, & Grandison, 1995;Patil & Reuter, 1988;Skudder, Brooker, Bonsey, & Alvarez Guerrero, 1986), air content (Jeurnink, 1995;Tirumalesh, Rao, & Jayaprakash, 1997), surface material (Foster, Britten, & Green, 1989;Foster & Green, 1990;Jeurnink, Verheul, Cohen, & de Kruif, 1996;Sharon & Fuller, 1994;Visser, Jeurnink, Schraml, Fryer, & Delplace, 1997) total solids, age of milk, season, addition of oxidizing agents (iodate, H 2 O 2 , dichromate) (Marshall, 1986;Skudder, Thomas, Pavey, & Perkin, 1981), addition of free fatty acids (Al-roubale & Burton, 1979), addition of phosphates (Burdett, 1974), etc. A number of attempts have been made earlier to cope with the problem of fouling which include design of fouling resistant equipment i.e.…”
Section: Introductionmentioning
confidence: 99%